Analisis Fitokimia terhadap Senyawa Aktif dalam Daun Carica Papaya sebagai Dasar Formulasi Kapsul - Kurniadi, Helman; Syafitri, Ulfah Eka; Alfiana, Dessinta; Framisa, Mentari; Hairani; Heldiana, Fitria (Biosel Biology Science and Education, 2025)
Papaya leaves (Carica papaya L.) are rich in secondary metabolites with pharmacological potential as antioxidants, anti-inflammatories, and antimicrobials. This study aimed to identify bioactive compounds in papaya leaves, develop simplicia and extracts as a basis for capsule formulation, and evaluate the characteristics and stability of the resulting capsules. The methods used included simplicia preparation, extraction using maceration with 70% ethanol, phytochemical analysis using specific reagent tests, and capsule formulation with appropriate excipients. The results showed that papaya leaf simplicia had a moisture content of ≤ 5%, extraction yielded a rendement of 9.6%, and active compounds such as alkaloids, flavonoids, and polyphenols were detected. Capsule formulations containing papaya leaf extract showed good characteristics, with a dissolution time reaching 80% within 30 minutes, and good stability during storage. Papaya leaf extract can be developed as a stable, effective, and pharmaceutically standardized herbal phytopharmaceutical capsule preparation to support natural medicine. Keywords: C. papaya, Secondary Metabolites, Maceration, Herbal Capsule, Phytochemistry